First record in midwestern region of the state of são paulo, brazil of typhlops brongersmianus vanzolini, 1976 (squamata: Typhlopidae) - de Arruda, Mauricio Papa; Almeida, Carlos Henrique L. N.; Rolim, Daniel C. [UNESP]; Maffei, Fábio (My University, 2011)
In this study we report on two new records of the blindsnake Typhlops brongersmianus for the municipality of Bauru, midwestern region of the state of São Paulo, Brazil. These records expand the geographic distribution currently known for this species in the state and contribute to the knowledge of snakes in southeastern Brazil. © 2011 Check List and Authors.
Keywords: Serpentes; Squamata; Typhlopidae; Typhlops